Modelling children’s independent territorial range by discretionary and nondiscretionary trips - Samia Sharmin; Md. Kamruzzaman; Md. Mazharul Haque (Journal of Transport and Land Use)
The decline of children’s independent mobility (CIM) is now a global concern. This study aims to identify the determinants of the territorial range (TR) of CIM, i.e., the geographical distance between home and places where children are allowed to wander. TR for both discretionary and nondiscretionary trips is studied based on data collected through a questionnaire survey, travel diary, and mapping of travel routes. The study sample was comprised of 151 children 9-14 years of age from Dhaka, Bangladesh. Built environment (BE) data were collected/derived through walkability audits of children’s walking routes and spatial analyses. Children’s TR was regressed by BE, socio-demographics, and perceptual factors. Three multiple regression models were estimated: overall TR, discretionary TR, and nondiscretionary TR. Results showed that children had a longer TR for nondiscretionary trips (664.14 m) compared to discretionary trips (397.9 m). Discretionary TR was largely explained by angular step-depth, street connectivity and the condition of the walking environment of the taken routes. In contrast, angular step-depth, the presence of commercial and retail land uses and the condition of the walking environment were found to be significant predictors of nondiscretionary TR. Children’s perception of social and physical dangers and their satisfaction with tree coverage in the neighborhood also influenced their TR. The findings can inform measures to be taken to expand TR in the urban environment.